1998
DOI: 10.1007/s11745-998-0194-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cultured arterial smooth muscle cells isolated from chicks upon cholesterol feeding

Abstract: We have developed cultures of smooth muscle cells (SMC) isolated from arterial hypercholesterolemic chicks (cholesterol-SMC). These cultures are suitable for the study at the molecular level of the changes in arterial SMC induced by a cholesterol diet. By using a strong dose of cholesterol (5%) for 10 d, we obtained very proliferative SMC which became foam cells after 30 d in culture. On the other hand, SMC cultures isolated from control-fed chicks had a lower growth rate than the SMC ones under the same cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…Twenty day-old chicken embryo pulmonary arterial smooth muscle cells (PASMCs) were isolated by enzymatic digestion as previously described [19,20]. In brief, proximal pulmonary arteries were isolated under aseptic condition and were cut into small pieces after removal of fat, adventitia, and connective tissue surrounding the arteries.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty day-old chicken embryo pulmonary arterial smooth muscle cells (PASMCs) were isolated by enzymatic digestion as previously described [19,20]. In brief, proximal pulmonary arteries were isolated under aseptic condition and were cut into small pieces after removal of fat, adventitia, and connective tissue surrounding the arteries.…”
Section: Methodsmentioning
confidence: 99%
“…SMCs were isolated from the aortic arch of the chicks as described elsewhere [17] with slight modifications and cultured in Dulbecco's Modification of Eagle's Medium (DMEM) supplemented with D-glucose (4.5 g/L), L-glutamate (0.584 g/mL), antibiotic cocktail composed of penicillin (100 μ g/mL) and amphotericin (0.25 μ g/mL) (Sigma-Aldrich, Inc.), as well as 10% (v/v) fetal bovine serum (FBS). Medium was buffered with bicarbonate and cultures were kept at 37°C in humidified atmosphere of 95% air and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Thus, chickens have been reported to readily develop hypercholesterolemia with a cholesterol-rich diet, producing atherosclerotic lesions in some cases [1416]. Preliminary studies demonstrated that a 20-day diet enriched with 5% cholesterol is sufficient to cause hypercholesterolemia and gives rise to lipid deposits in the main arteries that are similar to the fatty streaks observed in the first stages of atherosclerosis [17]. …”
Section: Introductionmentioning
confidence: 99%
“…SMC were isolated from the aortic arch of the chicks as described elsewhere with slight modifications [31] and cultured in Dulbecco's Modification of Eagle's Medium (DMEM) supplemented with D-glucose (4.5 g/l), L-glutamate (0.584 g/ml), antibiotic cocktail composed of penicillin (100 mg/ml) and amphotericin (0.25 mg/ml) (Sigma-Aldrich, Inc), and 10% (v/v) fetal bovine serum (FBS). Medium was buffered with bicarbonate, and cultures were kept at 37°C in humidified atmosphere (95% air, 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has proven suitable for in vitro study of the transformation into foam cells of SMC induced in vivo by cholesterol diet, isolating the cells before plaque formation [31]. Previous results with this model showed marked differences in proliferation and synthesis of DNA, RNA and protein between Ch-SMC and C-SMC, and these cell lines differed in lipid (especially cholesterol) synthesis and in the effects of inhibition on the first step of cholesterol biosynthesis [31,32]. In another study, Ch-SMC and C-SMC cultures showed altered HMG-CoA reductase activity and gene expression at transcriptional level [33].…”
Section: Introductionmentioning
confidence: 99%